Optimisation of a single-pass superconducting linac as a FEL driver for the NLS project - Bartolini, R; Christou, C; Han, J; Martin, I; Rowland, J; Venturini, M; Angal-Kalinin, D; Jackson, F; Muratori, B; Williams, P (2009)
In this paper we present the results of the optimisation of a single pass superconducting linac as a driver for the FELs of the UK's proposed New Light Source. The optimisation process requires the analysis of complicated electron beam dynamics in the presence of CSR, wakefields and space charge and has specifically taken into account the requirements for FEL operation in a seeded harmonic cascade scheme.